Changes in antagonist muscle coactivation after a simulated team handball match: A potential risk factor for ACL injury? - Zebis, M. K.; Bencke, J.; Birk, K.; Mortensen, P.; Kjaer, M.; Aagaard, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Most non-contact ACL-injuries in sports and exercise occurs in situations like landing, sidecutting or deceleration, which involve substantial eccentric quadriceps muscle forces (Bencke et al., 2000). Coactivation of the hamstring muscles is important for dynamic knee joint stabilization and to prevent or control excessive anterior ACL shear forces (Draganich & Vahey 1990, More et al. 1993). The present study examined the influence of exercise-induced muscle fatigue on antagonist hamstring coactivation during isolated knee joint movements involving maximal eccentric quadriceps contraction. Methods: Net knee extension torque, and quadriceps (VL,VM,RF) and hamstring (Bfcl,ST) EMG were obtained in female elite handball players during maximal voluntary isokinetic eccentric quadriceps action (KinCom; 10-90° ROM, 240°/s) pre and post a 50 min. simulated handball match. Antagonist hamstring EMG was expressed relative to the maximal agonist hamstring EMG recorded during maximal voluntary concentric hamstring contraction (10-90° ROM, 240°/s) (Aagaard et al. 2000). EMG and torque data were averaged in the 20-30° ROM (0° = full knee extension). Results After the simulated match procedure, maximal eccentric quadriceps contraction strength decreased by 13% (p<0.05) while concentric hamstring contraction strength decreased by 14% (p<0.05). Quadriceps agonist EMG remained statistically unchanged. In contrast, antagonist coactivation in the lateral hamstrings (Bfcl) decreased by 21% (p<0.05) (Fig.1). Discussion Antagonist hamstring coactivation provides stability to the knee joint by reducing anterior tibial displacement (Draganich & Vahey 1990) and internal tibial rotation (More et al. 1993), which in turn lowers the strain and stress in the ACL (Draganich & Vahey 1990, More et al. 1993). The present data confirms previous findings that lateral antagonist hamstring coactivation (Bfcl) is 2-3 fold greater than medial hamstring (ST) coactivation (Escamilla et al. 1998, Aagaard et al. 2000), which may represent an important mechanism to counteract excessive internal tibial rotation and corresponding elevations in ACL stress. In the present study a differential change in antagonist hamstring coactivation pattern was observed after the simulated match protocol, since lateral hamstring (Bfcl) coactivation decreased by 21% while medial hamstring coactivation (ST) remained unchanged. Given that lateral hamstring coactivation may counteract excessive internal tibial rotation and corresponding increases in ACL stress loading, the observed decrease in Bfcl antagonist coactivation may reflect a potential risk factor for increased ACL stress in the fatigued state. The present findings suggest that to protect the ACL from non-contact injury it may be useful to employ prophylactic neuromuscular training that teaches the athlete to maintain a high level of lateral hamstring coactivation throughout the time course of a match or training.